Estimation of Shear Stiffness of Interlayer Connection in Two-Layer Composite Beams Based on Analysis of Natural Frequencies - Perkowski, Zbigniew; Czabak, Mariusz; Gozarska, Karolina (Communications - Scientific letters of the University of Zilina, 2013)
The paper shows possibilities of testing composite two-layer beams with flexible connectors (like bolts in steel-concrete beams and nails in wooden-concrete ones) offered by analysis of their natural frequencies. It enables an estimation of shear compliance for the interlayer connection if Young’s moduli of layers are known thanks to finding the global minimum of function of errors between model and measured natural frequencies of beam. The considerations are illustrated by the results of our own laboratory-tests.